2016
DOI: 10.1111/jgh.13330
|View full text |Cite
|
Sign up to set email alerts
|

The roles of HOXB7 in promoting migration, invasion, and anti‐apoptosis in gastric cancer

Abstract: Our study suggests that HOXB7 has an oncogenic role in gastric cancer, which might be related to the modulation of Akt/PTEN activity to induce cell migration/invasion and anti-apoptotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
(74 reference statements)
2
25
0
Order By: Relevance
“…As we were primarily interested in direct interaction partners, we performed an in silico target prediction analysis of potential complementary sequence seeds and a complementary literature search to further identify miR-196b-5p targets with a putative influence on cancer cell migration. The process in its entirety identified 2 candidate genes, HOXB7 and GALNT5 that have been previously implicated in gastric and cervical cancer cell migration and/or invasion (34,36,37). In colorectal cancer, a study by Liao and colleagues reported that HOXB7 is significantly correlated with invasive and aggressive characteristics and poor survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As we were primarily interested in direct interaction partners, we performed an in silico target prediction analysis of potential complementary sequence seeds and a complementary literature search to further identify miR-196b-5p targets with a putative influence on cancer cell migration. The process in its entirety identified 2 candidate genes, HOXB7 and GALNT5 that have been previously implicated in gastric and cervical cancer cell migration and/or invasion (34,36,37). In colorectal cancer, a study by Liao and colleagues reported that HOXB7 is significantly correlated with invasive and aggressive characteristics and poor survival of patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, HOXC6 appears to promote colorectal cancer (CRC) cell proliferation and tumorigenesis [45]. Then, HOXB7 over-expression was observed in gastric cancer and ESCC [46,47]. Liu et al [16] reported that the abnormal expression of HOTAIR promotes NSCLC cell migration and metastasis, partially via the down-regulation of HOXA5.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the PI3K/AKT/c-Myc axis was modulated by HOXB7 to facilitate the acquisition of cancer stem-like properties in hepatoma cells. It has also been reported that gastric cancer cell metastasis is promoted by HOXB7 via the PI3K/AKT pathway [6, 32, 33]. The AKT pathway was involved in EMT and carcinogenesis via the up-regulation of Slug [34].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of homeobox genes is frequently detected in a variety of cancers [5]. Homeobox B7 (HOXB7), a member of homeobox gene family, has been shown to be involved in several cancers, including gastric [6], oral [7], pancreatic [8] and breast cancer [9]. As an important transcription factor, HOXB7 regulates many cancer cell functions, including proliferation, invasion, migration, angiogenesis and epithelial-mesenchymal transition (EMT) [10].…”
Section: Introductionmentioning
confidence: 99%